Reflections on the economic crisis one year on: an interview with Huginn Freyr Þorsteinsson - Giorgio Baruchello; Huginn Freyr Þorsteinsson (The University of Akureyri, 2011)
he Editors of Nordicum-Mediterraneum interviewed Huginn Freyrr Þorsteinnson, Political Advisor to the Icelandic Minister of Finance, on the international economic crisis, to which a special section was devoted in the previous issue of the journal. Given the left-wing composition of the current parliamentary majority in Iceland and the affiliation of the current members of the Icelandic cabinet, questions are asked while keeping in mind the traditional aims, policies and interpretations of the left.